1994
DOI: 10.1093/ptj/74.10.951
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Selected Stimulus Waveforms on Pulse and Phase Characteristics at Sensory and Motor Thresholds

Abstract: The authors concluded that all five studied waveforms were effective at threshold excitation of peripheral sensory and motor nerves. Of the five waveforms, the symmetrical biphasic waveform, having a low total pulse charge, may be the preferred waveform, and the 25 symmetrical pulses and amplitude-modulated waveforms may be considered the least preferred due to high total pulse charge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 0 publications
2
48
0
7
Order By: Relevance
“…Advancements in the type of waveforms used during stimulation have been noted in other forms of neuromodulation. Monophasic wave pulses have been traditionally used for intravesical electrical stimulation therapy, but several studies [11][12][13][14] found that biphasic waveforms were a better alternative to monophasic waves. Specifically, the charge-balanced biphasic waveforms had an equal or lower peak current and peak voltage, as well as phase change.…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in the type of waveforms used during stimulation have been noted in other forms of neuromodulation. Monophasic wave pulses have been traditionally used for intravesical electrical stimulation therapy, but several studies [11][12][13][14] found that biphasic waveforms were a better alternative to monophasic waves. Specifically, the charge-balanced biphasic waveforms had an equal or lower peak current and peak voltage, as well as phase change.…”
Section: Discussionmentioning
confidence: 99%
“…19) Net current flow will be theoretically zero beneath two electrodes of TENS unit with symmetrical biphasic waveform, while the build-up of ion concentrations with a certain charge will occur beneath electrodes of TENS unit with monophasic waveform. 49) As excess build-up of ion concentrations is more likely to cause the adverse skin reactions, almost current TENS units adopt the biphasic waveform for the safety. 19) Sometimes, asymmetrical biphasic waveform was adopted for the mild accumulation of ions, resulting in slight concentration preferential polarity beneath the electrodes.…”
Section: Waveformmentioning
confidence: 99%
“…The stimulation was performed with a monopolar square pulse duration of 200 µsec. Medium pulses (~200 µsec) were utilized to ensure torque generation and to avoid muscle fatigue and nociceptor activation [24][25][26][27][28] .…”
Section: Motor Threshold Measurementmentioning
confidence: 99%